Estrategias ambientales y reportes de sostenibilidad en empresas petroleras (2018)
This monograph sought to identify the environmental strategy of 5 oil companies (Gran Tierra, Canacol Energy, Mansarovar, Ecopetrol and Hocol) based on the GRI sustainability reports and the information contained in the web pages of each of them. The investigation addressed the environmental deterioration that the oil industry has caused on the different environmental factors (air, land and water) and the responsibility of the companies to assume the consequences of their activities. From the sustainability reports, the mission and vision of each of the companies were identified, in order to identify the contemplation of the environmental strategies registered in these management commitments and if they corresponded with those defined in their sustainability reports.